ANALYSIS OF CLINICAL SIGNS OF A PATIENT'S OSTEOARTHROSIS - Tuksanova Zebiniso Izatulloyevna (Scholar Express Journals, 2022)
This article describes the clinical characteristics of female and male patients aged 35 to 65 with a diagnosis of osteoarthritis
Keywords: Knee joint; chondroitin sulfate; rehabilitation; osteophyte